Learning styles of Centennial students in a social laboratory - Mellink-Méndez, Sialia Karina; López Leyva, Josué Aarón; Murillo-Aviña, Gloria Janeth; Chapela-Cerecero, José Esteban (My University, 2026)
The stakeholder’s participation is crucial to analyzing wicked problems. To explore the connection with Centennial stakeholders, this research presents an exploratory, cross-sectional, and quantitative analysis of learning styles (LS) according to Kolb’s theory for Centennial stakeholders in a transition design approach. In general, 5 research hypotheses were proposed to determine findings that allow improving the design and development of a social laboratory within the framework of educational institutions as part of a process innovation where students become more involved with wicked problems. The results show that there is some predominant LS, accommodation (LS1) related to feeling and doing, and diverging (LS3) related to feeling and watching. To conclude, according to our survey, Centennial stakeholders have a balance concerning LS that must be considered as part of the design of the approach to wicked problems.
Journal of Education and Learning
Keywords: Learning styles of Centennial students in a social laboratory; Learning styles of Centennial students in a social laboratory; Learning styles of Centennial students in a social laboratory; Learning styles of Centennial students in a social laboratory; Learning styles of Centennial students in a social laboratory; Campus Ensenada